First Report of Mcadam’s Scorpionfish Parascorpaena mcadamsi (Fowler, 1938) from Indian Waters - Mohapatra, Anil; Tudu, Prasad Chandra; Ray, Dipanjan (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.